“Proyecto de Factibilidad para la creación de una empresa dedicada a la producción y comercialización de bebida embotellada de horchata, endulzada con Stevia en la Ciudad de Loja - Pucha Pucha, Lenin Ivan (2018)
The purpose of this project is to determine the economic feasibility for the implementation of a production and commercialization company of bottled horchata sweetened with stevia in the city of Loja, this being a new product of excellent quality and price. The methodology used is based on usual methods such as the deductive and inductive method, these methods allowed us to obtain all the information that the project requires by helping with techniques such as natural observation, surveys, structured interview and the size of the sample with which it was possible to obtain the number of surveys that were applied. In order to carry out this feasibility project, several objectives were proposed, which begin with the market study in which the following is detailed: market segmentation, analysis of demands; thus having the potential claimants of the product are 190,178 people from the city of Loja, while the actual claimants are 180,669 people and the effective claimants are 178,862 people. Consecutively, the technical study was carried out analyzing the installed and used capacity of 1,051,200 and 239,200 liters per year in order, the macro and micro location, the production process, plant distribution and requirements. Then, the organizational study was carried out, which contains the constitution minutes, an executive, advisory, support assistant, and operative level was established, to then make the different organizational charts and function manuals. The financial study details the investment that is $ 50,114.69, the financing will be made through own and external capital, we also have the cost budgets, the retail price for the first year is $ 0.80 cents for each ½ liter of horchata, income from sales that are for the first year of $ 191,360.00; the equilibrium point that regarding sales for the first year is of $ 125,860.13 and depending on the installed capacity is of 65.77%, the financial statements and the cash flow; finally the financial evaluation was carried out through the different indicators such as: Net Present Value (NPV) which is of $ 118.688,91 the Internal Rate of Return (IRR) which is 57.53%, the Analysis of Sensitivity with cost increase corresponding to 10.50% and with decrease in 5 income corresponding to 8.63%, Cost Benefit Ratio (RBC) that indicates that the profit is 21 cents for each dollar invested and the Period of Capital Recovery (PRC), which tells us that the investment will recover in 2 years 4 months and 3 days. Finally to the conclusions reached we have: that in all parameters of the financial evaluation of this project were positive, which allows to verify and confirm its feasibility and future implementation.